Educational Potential of New Media - Kazak, Maria Yu.; Karpenko, Irina I.; Korochenskiy, Aleksandr P.; Polonskiy, Andrey V.; Tiazhlov, Yan I.; Ushakova, Svetlana V. (Journal of History Culture and Art Research, 2017)
Digitalization of the mass media, which has radically changed the information environment, creates new opportunities for self-education and upgrowth of the audience. The paper defines the communicative and cultural status of new media, characterizes the socio-cultural and technological aspects of their dynamics; substantiates the necessity of elaborating mechanisms for systematization of heterogeneous information flows and elaborating criteria for their evaluation in the era of globalization of the media sphere, what implies a qualitatively different level of media competence of the audience, provided with such factors as media education, media coverage, media criticism. The definition of concepts "media competence", "media enlightenment", "media education", "media criticism" is given and their functional areas are delineated. Social networks are considered as an important tool for media enlightenment which provides significant opportunities for promoting cultural achievements in the new media environment.